A bivalent COVID-19 mRNA vaccine elicited broad immune responses and protection against Omicron subvariants infection - Jun Liu; Li Wang; Alexandra Kurtesi; Patrick Budylowski; Kyle G. Potts; Haritha Menon; Yilin Tan; Philip Samaan; Xinan Liu; Yisen Wang; Queenie Hu; Reuben Samson; et al. (npj Vaccines)
Abstract Continuously emerging SARS-CoV-2 Omicron subvariants pose a threat thwarting the effectiveness of approved COVID-19 vaccines. Especially, the protection breadth and degree of these vaccines against antigenically distant Omicron subvariants is unclear. Here, we report the immunogenicity and efficacy of a bivalent mRNA vaccine, PTX-COVID19-M1.2 (M1.2), which encodes native spike proteins from Wuhan-Hu-1 (D614G) and Omicron BA.2.12.1, in mouse and hamster models. Both primary series and booster vaccination using M1.2 elicited potent and broad nAbs against Wuhan-Hu-1 (D614G) and some Omicron subvariants. Strong spike-specific T cell responses against Wuhan-Hu-1 and Omicron subvariants, including JN.1, were also induced. Vaccination with M1.2 protected animals from Wuhan-Hu-1 and multiple Omicron subvariants challenges. Interestingly, protection against XBB.1.5 lung infection did not correlate with nAb levels. These results indicate that M1.2 generated a broadly protective immune response against antigenically distant Omicron subvariants, and spike-specific T cells probably contributed to the breadth of the protection.